The winds of altair eaudiobook - Bova, Ben (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2013)
Earth is an old planet, and her teeming masses are running out of resources—and time. It is up to men such as Jeff Holman to discover a haven for Earth's millions. Altair VI is one such planet, and Holman is determined to transform this world into one where the human race can survive. Star probes long ago informed Earth that Altair VI had a flourishing ecology with one very tough beast at the top of the food chain, one that will have to be dealt with before the human colony ships arrive. The beast is not only tough, it is as smart as a man. Holman is faced with a soul-wrenching decision—for to make Altair VI habitable for humans, all native life must die.